Identification Of Nutritional Content, Taxonomy and Processed Products Of Campolay Fruit (Pouteria Champeciana) - Rahmi Dzulhijjah; Mohd Sarli; Dina Arafa Shabayek (Yayasan Rumah Ilmu Professor, 2022)
Pouteria champeciana (campolay) is a type of tropical fruit grown in Indonesia. Though the nutritional content of the fruit has the potential as a processed food product. This study analyzed taxonomy, vitamin C, total carotene, total sugar content and minerals (Ca, Mg, K, Na) in campolay fruit and processing campolay fruit flesh into processed food products. This type of research is descriptive research. Campolay fruit obtained from Tarogong Kidul, Garut Regency, West Java. Analysis of vitamin C levels in campolay fruit flesh using the iodometric titration method, total carotene using spectrophotometric methods, testing total sugar content using the Nelson Somogyi method and mineral testing (Ca, Mg, K, Na) on campolay fruit using AAS. The results of the analysis showed that the level of vitamin C in the campolay fruit flesh was 215.685 (mg/100g), total carotene of 31.185 (mg/100g), total sugar content 18.085% and minerals (Ca, Mg, Na, K) on a campolay fruit of 1124.481 (ppm), 358.914 (ppm), 431.996 (ppm) and 8183.999 (ppm). Campolay fruit processing can be used in a variety of food products such as smoothies, cup cakes, cereal flakes, puddings and jelly drinks.